Immobilization of horseradish peroxidase on multi-armed magnetic graphene oxide composite : improvement of loading amount and catalytic activity - Rong, Junhui (Array, 2019)
In this study, a novel type of multi-armed polymer (poyltehylene glycol, PEG) magnetic graphene oxide (GO) composite (GO@Fe3O4@6arm-PEG-NH2) has been synthesized as a support for immobilization of horseradish peroxidase (HRP) for the first time. The loading amount of HRP was relatively high (186.34 mg/g) due to the surface of carrier material containing a large amount of amino groups from 6arm-PEG-NH2, but degradation rate of phenols was also much higher (95.4 %), which is attributed to the synergistic effect between the free HRP (45.4 %) and the support material of GO@Fe3O4@6arm-PEG-NH2 (13.6 %). Compared with the free enzyme, thermal, storage and operational stability of the immobilized HRP improved. The immobilized HRP still retained over 68.1 % activity after being reused 8 times. These results suggest that the multi-armed magnetic composite has good application prospect for enzyme immobilization.